LITERASI MEDIA PROMOSI UMKM PKK RW 017 BABADAN BANGUNTAPAN, KAB BANTUL, DI YOGYAKARTA - Novianti, Dewi; fatonah, Siti (Dharma: Jurnal Pengabdian Masyarakat, 2020)
The covid-19 pandemic outbreak has made the economy experience a decline. Economic activity is increasingly uncertain. This is also experienced by housewives RW17 Babadan, Banguntapan, Bantul Regency. Family Welfare Education women help the family economy with culinary businesses. They established micro, small and medium enterprises. The first problem is that these housewives experience difficulties in selling, due to their limited movement to offer their culinary works to consumers. Second, the understanding of media literacy in using social media as a new media is still lacking and thirdly, the understanding and ability to make messages is minimal through social media. Community service methods are discussion, focuse group discussion, socialization, and media literacy training. The solution to this problem is to hold training and mentoring on understanding media literacy in carrying out sales promotion activities. In addition, by holding skills training in documenting culinary products and in packaging messages through social media. The conclusion is that community empowerment by providing promotional media literacy makes them understand the benefits of using modern communication tools and new media. In the end, they were able to take advantage of smartphones to sell their products.